2016
DOI: 10.1103/physrevlett.117.056001
|View full text |Cite
|
Sign up to set email alerts
|

Multifold Increases in Turing Pattern Wavelength in the Chlorine Dioxide-Iodine-Malonic Acid Reaction-Diffusion System

Abstract: Turing patterns in the chlorine dioxide-iodine-malonic acid reaction were modified through additions of sodium halide salt solutions. The range of wavelengths obtained is several times larger than in the previously reported literature. Pattern wavelength was observed to significantly increase with sodium bromide or sodium chloride. A transition to a uniform state was found at high halide concentrations. The observed experimental results are qualitatively well reproduced in numerical simulations with the Lengye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…At this point, we are ready to test the recently published method of adding halide ions to the CDIMA system to increase the wavelength of the Turing patterns. 20 Although, it was originally used to modify patterns in a one-side-fed open reactor, we found that it can be applied in closed two-layer systems as well. We have chosen Br – ions, which were added to the ClO 2 -free initial side to avoid the oxidation of Br – by ClO 2 during the soaking of the gel pieces.…”
Section: Resultsmentioning
confidence: 99%
“…At this point, we are ready to test the recently published method of adding halide ions to the CDIMA system to increase the wavelength of the Turing patterns. 20 Although, it was originally used to modify patterns in a one-side-fed open reactor, we found that it can be applied in closed two-layer systems as well. We have chosen Br – ions, which were added to the ClO 2 -free initial side to avoid the oxidation of Br – by ClO 2 during the soaking of the gel pieces.…”
Section: Resultsmentioning
confidence: 99%
“…Numerical simulations of equations (2.1)–(2.2) show very good agreement with experiments, as shown in figure 2. The LE model has also been modified to account for a variety of external factors, such as competitive binding interactions to the immobile substrate [41] or photoinhibition [42,43].
Figure 2Comparison of labyrinthine Turing patterns in ( a ) the CDIMA reaction–diffusion system and ( b ) the LE model.
…”
Section: Early Chemical Turing Patternsmentioning
confidence: 99%
“…Many recent studies of chemical Turing patterns use the CDIMA reaction in a CFUR, where the patterns form in a quasi-two-dimensional gel with one-sided feeding [14,41,45,46]. A schematic for the experimental setup is shown in [14].…”
Section: The Chlorine Dioxide-iodine-malonic Acid Reactionmentioning
confidence: 99%
See 2 more Smart Citations